(untitled) (Journal of Health Sciences, 2016)
Introduction: Diffusion weighted imaging (DWI) is a form of magnetic resonance imaging (MRI) based on measuring the random Brownian motion of water molecules within a tissue. The aim of this study was to show the significance of diffusion-weighted imaging (DWI) in differentiating pancreatic cystic formations from normal pancreatic parenchyma using MRI 1.5 T.Methods: A total of 52 patients were included in the study (25 with pancreatic cystic formations and 27 with normal MRI findings of the pancreas). DWI technique was used with b values of 0.500 and 1 000 mm2/s at 1.5 T. The signal intensity was measured, as well as apparent diffusion coefficient (ADC). Visual estimation of the signal intensity of detected cystic lesions was performed and compared to the normal appearance of pancreas.Results: The highest signal intensity of the cystic lesions with hyper-signal was observed with DWI b0 value in the pancreatic head (M 185.1 ± 47.205, p < 0.05). Similarly, the highest apparent diffusion coefficient (ADC) value of the cystic formations with hyper-signal was observed in the pancreatic head (2.09 x 10-3 mm2/s, p < 0.05). In the group with healthy pancreas, the highest signal intensity was observed with DWI b0 value (M 76.40 ± 18.28, p < 0.05). The observed ADC value in this group was 1.21 x 10-3 mm2/s in the head, 1.24 x 10-3mm2/s in the neck, 1.21 x 10-3mm2/s in the body, and 1.06 x 10-3mm2/s in the tail; p > 0.05.Conclusions: Differences in signal intensity and ADC values have an important diagnostic value in differentiating the cystic formations from normal pancreatic parenchyma in MRI examination.